Social Networking Sites and Deviance among Youth in Islamabad, Pakistan (European Journal of Behavioral Sciences, 2018)
The digital media transform the social scenario of Pakistan. We are living in an era of information explosion. Social networking sites such as Facebook, Twitter, Skype, Instagram, and WhatsApp provide a platform to express our thoughts and share it with other people. Social networking apps are utilized for information, knowledge, fun, music, images, and videos. It creates both positive and negative influences on youth. Social media facilitated deviance among youth such as pornography, blackmailing, and online harassment. The current study aimed to explore the role of social networking sites in promoting deviance among youngsters’ life. The present cross-sectional research applied a quantitative methodology to explore this phenomenon. The population comprised both males and females between the age of 21-24 and the universe confined to Islamabad. The sample size was 323 youngsters from International Islamic University Islamabad, Pakistan. The researcher administered a survey conducted by utilizing a questionnaire. Stratified random sampling used to locate the respondents in the faculty of social science. Univariate and bivariate analysis of the field data done by SPSS. Majority of the respondent (98.3%) used social networking sites and 56.6% respondents said online harassment is done by these sites which effect women dignity.68.9% youngsters said social networking apps promote deviance among youth and 72.3% said social networking apps promote the abusive language. On this basis of the findings, it can be concluded that social media usage should be monitored and parents should have awareness about the deleterious effect of social networking.